Didiclis chiangdaoensis (Selaginellaceae), a new species of the Bisulcata group from northern Thailand - Hu, Yu-Ping; Zhang, Li-Bing; Suwanmala, Orawanya; Chantanaorrapint, Sahut; Zhou, Xin-Mao (Phytotaxa, 2025)
A new lycophyte species, Didiclis chiangdaoensis (Selaginellaceae), is described and illustrated from Chiang Mai Province, Thailand. The new species belongs to the Bisulcata group and can be easily distinguished by its extremely small plants (less than10 cm) and the entire margins of sterile leaves.